2010
DOI: 10.1080/10942910802571745
|View full text |Cite
|
Sign up to set email alerts
|

Selected Geometric Characteristics, Density, and Mechanical Properties of Unsplit Pistachio Nut

Abstract: In this study, several physical properties of unsplit pistachio nut were determined as functions of moisture content. By increasing moisture content from 5 to 20% all geometric characteristics increased linearly. Also, apparent and bulk density increased from 803 to 872 kg/m3 and from 458 to 575 kg/m3, respectively, while porosity decreased from 43% to 34%. Coefficient of static friction of the sample nuts on galvanized iron, plywood, and rubber surfaces increased linearly with moisture content. Nut splitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…These results can be explained with contraction of the kernel as a result of decreasing the moisture. Similar results have been reported by Altuntas and Yildiz [12] for faba bean grains; Aktas et al [6] for almond nut; Dursun and Dursun [8] for caper seed; Kaleemullah and Gunasekar [18] for arecanut kernel; Maghsoudi et al [21] for unsplit pistachio nut; Razavi et al [24] for pistachio nuts and kernels; Abalone [28] for amaranth seeds; Bart-Plange and Baryeh [29] for cocoa bean, etc. They showed that physical properties increase numerically with an increase in moisture content.…”
Section: Physical Propertiessupporting
confidence: 85%
See 2 more Smart Citations
“…These results can be explained with contraction of the kernel as a result of decreasing the moisture. Similar results have been reported by Altuntas and Yildiz [12] for faba bean grains; Aktas et al [6] for almond nut; Dursun and Dursun [8] for caper seed; Kaleemullah and Gunasekar [18] for arecanut kernel; Maghsoudi et al [21] for unsplit pistachio nut; Razavi et al [24] for pistachio nuts and kernels; Abalone [28] for amaranth seeds; Bart-Plange and Baryeh [29] for cocoa bean, etc. They showed that physical properties increase numerically with an increase in moisture content.…”
Section: Physical Propertiessupporting
confidence: 85%
“…The results are in agreement with Singh and Goswami [11] who reported a decrease in energy absorbed by cumin seed with increasing in moisture content. Aktas et al [6] obtained a similar trend for some almond cultivars, whereas Maghsoudi et al [21] showed that greater energy is needed to split the pistachio nut at higher moisture content.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Practical uses include as a fire starter, as a medium for orchids, as an additive for wood items, as an animal feed, etc. Unsplitted (closed shell) pistachio nuts are used as snack food . However, recycling in more valuable applications such as filler for appropriate polymeric matrixes or for activated carbon production should be preferred for a natural waste .…”
Section: Introductionmentioning
confidence: 99%
“…It is referred to as the “green gold tree” due to its high economic value [3], [4]. Its origin is still indeterminate, but most experts come to an agreement that it probably originated in the Middle East [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%